2012
DOI: 10.1364/ol.37.004302
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of nanostructured TiO_2thin films and their application as antireflection coatings on infrared detectors

Abstract: Oblique-angle deposited titanium dioxide (TiO(2)) nanorods have attracted much attention as good antireflection (AR) coating material due to their low n profile. Therefore, it is necessary to better understand the optical properties of these nanorods. TiO(2) nanorods grown on glass and Si substrates were characterized in the visible (0.4-0.8 μm) and infrared (2-12 μm) regions to extract their complex n profiles empirically. Application of these nanorods in multilayer AR coatings on infrared detectors is also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…TiO 2 shows high temperature and high electrical resistance as well as high hardness, low optical absorption, and biocompatibility [16,17]. It has been used as an antireflection coating on infrared detectors [18], optical resonance filters [19] or as planar waveguiding structures [20]. It has been shown that when TiO 2 overlay is deposited on LPG with sol-gel method it adsorbs water molecules and can be applied for humidity sensing [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 shows high temperature and high electrical resistance as well as high hardness, low optical absorption, and biocompatibility [16,17]. It has been used as an antireflection coating on infrared detectors [18], optical resonance filters [19] or as planar waveguiding structures [20]. It has been shown that when TiO 2 overlay is deposited on LPG with sol-gel method it adsorbs water molecules and can be applied for humidity sensing [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Various structures including randomly or periodically textured surfaces, nanoparticle arrays and plasmonic nanostructures have been investigated both theoretically and experimentally [7][8][9][10]. Majorities of fabrication methods have been developed such as vapour-liquid-solid, solution-liquid-solid, metal-assisted chemical etching, nano-imprint lithography, oblique-angle deposition (OAD), atomic layer deposition (ALD) technique etc [9][10][11][12][13][14][15][16][17][18][19]. Xi et al fabricated five-layered graded-index films with TiO 2 /SiO 2 nanorods on aluminium nitride substrate by OAD at a vapour incident angle of 87° [11].…”
Section: Introductionmentioning
confidence: 99%
“…Anatase titanium dioxide (TiO 2 ) thin films are chemically stable, possess a high refractive index and an excellent transmittance in the visible range [15][16]. Therefore, they are extensively used in photocatalytic [17][18] and optical applications [19][20].…”
Section: Introductionmentioning
confidence: 99%